Implementing local planetary health: Case study of Blue Mountains, Australia. (13th August 2022) - Robson, Eleanor; Crabtree‐Hayes, Louise; Langevad, William; Zhong, Hua Flora; Barrett, Kim; Salazar, Juan Francisco
Abstract: Planetary health is a concept that emerged from public health and is of central interest for geographers. Blue Mountains City Council (BMCC) launched its planetary health initiative in 2020, which is a first instance of it being adopted by an Australian local government as a sustainability policy framework. This article presents an initial case study arguing for and testing how to gain empirical insights from developing local planetary health initiatives. Using an online survey of Blue Mountains residents from 2020, we elucidate key opportunities and challenges associated with implementing planetary health in local contexts. We found that respondents experience the impacts of environmental change in varied ways and want to do more to address environmental change. They demand action from governments and others to act, yet do not understand well the mechanisms available to local governments to undertake such action. We also established that planetary health shows promise in its ability to accommodate diverse and scalar experiences and action from personal to communal. Thus, our key claim is that it could be an inclusive basis upon which local governments and communities can deliberate and make decisions about sustainability. However, local governments could experience difficulties in implementing planetary health should deliberation not improve community understanding of the levers available to local government to act on environmental change and the nature of shared responsibility for place‐based sustainability. We suggest geographers could do more work on such matters. Abstract : Planetary health is a concept that emerged from public health, and Blue Mountains City Council's planetary health initiative is a first instance of it being adopted as a sustainability policy framing by a local government. Using an online survey of Blue Mountains residents from 2020, we elucidate key opportunities and challenges associated with implementing planetary health in local contexts. Planetary health shows promise in its ability to accommodate diverse and scalar experiences and actions from personal to communal. Thus, it could be an inclusive basis upon which local governments and communities can deliberate and make decisions about sustainability. At the same time, local governments could experience difficulties implementing planetary health should deliberation not improve community understandings of both the levers available to local government to act on environmental change and the nature of shared responsibility for place‐based sustainability.